A microfluidic approach for studying microcolonization of Escherichia coli O157:H7 on leaf trichome‐mimicking surfaces under fluid shear stress. Issue 6 (25th February 2022) - Mok, Jin Hong; Niu, Ye; Yousef, Ahmed; Zhao, Yi; Sastry, Sudhir K.
Abstract: Escherichia coli O157:H7 have previously been associated with disease outbreaks associated with leafy green vegetables. However, the physical mechanisms that determine the spatial organization of bacteria onto leafy greens are still not clear. Microfluidics with embedded trichome‐mimicking microposts were employed to investigate the role of shear flow and configuration of trichomes on E. coli O157:H7 microcolonization. We characterized the three‐dimensional microcolonization of green fluorescent protein (GFP)‐tagged E . coli O157:H7 using multiphoton fluorescence microscopy and compared their differences under static (no flow; incubated for 36 h at 37°C) and fluid shear conditions (750 nl/min for 36 h at 37°C). For micropatterned trichome arrays, we demonstrated that natural wax‐mixed polydimethylsiloxane retains similar topographies and contact angles to the surface of trichome‐bearing leafy greens. Our results showed that E . coli O157:H7 under fluid shear stress aligned their colonization parallel to the direction of flow. In a static condition, their colonization had no preferential alignment, with statistically similar angular distributions in all directions. In addition, depending on dimensions of the trichome arrays and flow conditions, different bacterial microcolonization patterns grew radially from initial attachment; they formed into filamentous structures and developed into bridges by surface hydrophobicity and flow‐induced shear with a nutrient‐rich medium. Collectively, these results demonstrate how the consequences of bacterial colonization in response to shear flow can affect pathogenic bacterial contamination of leafy greens and biofilm architectures. Abstract : Herein, the authors assessed the three‐dimensional configurations of Escherichia coli O157:H7 microcolonization to an array of artificially fabricated trichomes of leaf surfaces in a microfluidic channel. The colonization of GFP‐tagged E. coli O157:H7 was characterized under static and continuous‐flow conditions. These results demonstrate how shear flow can affect pathogenic bacterial contamination of leafy greens and biofilm architectures.